Sustained censorship in GB (2026-05) (United Kingdom) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in United Kingdom. Data sourced from OONI.
Censorship Incident ID: GB-2026-0040. Severity: critical. Confidence: 69%